Alloying effects in high temperature molten salt corrosion. (1st April 2022) - Ghaznavi, Touraj; Bryk, Mariusz A.; Persaud, Suraj Y.; Newman, Roger C.
Abstract: This study investigates dealloying of Fe-(Cr)-Ni model alloys in molten chloride salts that simulate the heat-transfer circuits of molten salt nuclear reactors. Classical dealloying with porosity formation is observed as the dominant form of corrosion at low homologous temperature, and the usual, fundamental, geometric parting limit for dealloying, 55–60 at% of the reactive element(s) (Fe and Cr), is decreased by several percent. This deviation is due to increased surface diffusivity of the more-noble element, Ni, in molten Cl salts. To better highlight deviations from conventional dealloying theory, results are compared with dealloying of similar Fe-(Cr)-Ni alloys in concentrated caustic solutions. Highlights: Dealloying with porosity formation occurs in Fe-(Cr)-Ni alloys in molten Cl salts. Operative mass transport is "percolation dealloying" at low homologous temperature. Microporous structure has ligaments with Fe- and Cr-rich core and Ni-rich shell. Dealloying threshold, at% of less-noble element(s), decreased by several percent. Reduced parting limit is due to increased surface mobility of Ni in molten Cl salts.